DESIGN OF BUSINESS RECORD SIMULATION APPLICATIONS AS A TOOL TO LEARNING RECEIVE LEARNING COLLEGE MANAGEMENT - Azizah Azizah; Isnaini Nurkhayati (Admisi dan Bisnis, 2017)
The retail industry is seen experiencing a very rapid growth and growing. Given the growingdevelopment of retail business and the importance of the acquisition of retail business, thestudents of Business Administration Department are equipped with subjects studying the retailbusiness, the subjects of Retail Management and Retail Practice. However, to date, the deliveryof such material is only done theoretically and only by manual recording on paper. Thiscertainly makes the retail courses less than the maximum in providing an understanding andexperience of the actual retail business to the students. For that purpose, a retail businesssimulation application can provide a more realistic picture to students in managing retailbusiness. In this study, the first thing to do is to do an analysis of what activities in the retailbusiness process will be displayed in the simulation. After that conducted data collection relatedto all business processes. The next step is to design the simulation system. Once the system flowis completed, it will create interface design and system design in it which is the basis ofprogramming simulation application. After the program is completed it will be tested todetermine whether or not there is error of the system.